Potensi penggunaan asap cair sebagai antiseptik di klinik gigi : studi pustaka - Wibisono, Gunawan; Skripsa, Tira Hamdillah; Prabowo, Yoghi Bagus; Boedi, Rizky Merdietio (jitek, 2022)
Aseptic quality is a crucial aspect of successful dental care attainment. Various oral microbes can increase the chance of failure in dental treatment. Multiple efforts have been made to improve the aseptic quality. It is known that the antiseptics used were costly and has numerous side effects. Natural antiseptics such as liquid smoke may be a potential substitute. This research aimed to explore the potential of liquid smoke as an antiseptic in dentistry. A systematic literature search was conducted in the electronic database of PubMed/Medline, ScienceDirect, and Google Scholar using PRISMA guideline. A structured search using the Boolean string “liquid smoke AND antimicrobial AND antibacterial” was performed. Initially, 115 potential articles were discovered. After removal of duplicates and checking the availability of full-text read, eleven studies were included. Liquid smoke with 1.5-50% concentration can eliminate S. mutant, S. sanguis, S. aureus, S. epidermidis, L. acidophilus, L. salivarius, E. faecalis, P. gingivalis and C. albicans. It was also reported that it has a particular effectiveness for the disinfectant and wound healing. Liquid smoke can eliminate both oral bacterial and fungi. Further research should explore the safety aspects of utilizing liquid smoke in dental clinics.